PENGARUH PENGETAHUAN AKUNTANSI, PENGALAMAN USAHA DAN MOTIVASI KERJA TERHADAP PERSEPSI PENGGUNAAN INFORMASI AKUNTANSI PADA PELAKU UMKM DI DESA NITA - Elisabeth Florensia Anjeli; Maria Nona Dince; Yustina Olivia Dasilva (Universitas Nusa Nipa Maumere, 2025)
This research aimed to determine whether accounting knowledge, business experience, and work motivation influence the perception of using accounting information among MSMEs actors in Nita Village. The method used was a quantitative method. The population in this research consisted of all MSMEs actors in Nita Village, totalling 80 people. The sample used in this research was determined by Slovin's formula with a 10% margin of enor, resulting in a sample size of 44 people. The sampling technique used in this research was Simple Random Sampling. The data used in this research were quantitative data obtained through respondents completing questionnaires using a Likert seale. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) program, version 2025. The research results showed that accounting knowledge influences the perception of using accounting information among MSMEs actors in Nita Village, as indicated by a t-statistic value of 2.789, which was greater than the t-table value of 2.021, or 2.789 > 2.021. Business experience did not influence the perception of using accounting information among MSMEs actors in Nita Village, as indicated by a t-statistic value of 0.101, which was smaller than the t-table value of 0.920, or 0.101 <0.920. Work motivation did not influence the perception of using accounting information among MSMEs actors in Nita Village, as indicated by a t-statistic value of 2.318, which was greater than the t-table value of 0.021. or 2.318>0.021.